The Impact of Outbound Training Activity on Organization Mission Statement (Case in Education Mission Statement MMT-ITS) - Handiwibowo, Gogor Arif; Suef, Mokhamad (IPTEK The Journal for Technology and Science, 2025)
In the review of organizational behavior, effective organizations require process variables component. One of the process variables form is the existence of training design for members of the organization. The training can encourage an organization member to be an effective member. Outbound training as one of the training methods has been popular since the 1990s and has become a trend for human resource development. As a training method, outbound training with several specific goals has been widely researched and has proven to have a positive impact on team building in teamwork. On the other hand, an organization has formulated an organizational vision in the strategic management context. The organization vision than set the mission statements to coordinate of proposed goals of the organization. Furthermore, every activity in an organization should reflect and base on mission statements value to achieve its strategic competitiveness. This research examines the role of outbound training objective as a contingency factor which affects the mission statement of an organization. The research took the case in MMT-ITS as the education organization. The outbound training objective divide into two objectives, the scientific objective, and internal objective and set as the variable factor. The mission statement studied in this case is education mission statement in MMT-ITS.